Paroemia readings in non-liturgical (četi) copies of the Book of Exodus - Желязкова, Веселка (Studia Ceranea, 2016)
The article studies the correlation between the Slavonic liturgical and non-liturgical versions of the Book of Exodus. The linguistic-textological data as well as some variant readings allow us to conclude that during the translation of the non-liturgical (full, četi) text of the Book of Exodus the translator did not use already translated paroemias. There is every reason to associate this new translation with the texts translated or revised in Preslav in the 10th century. The liturgical (paroemias) readings were included in the full copies of Exodus later and thus partially replaced the non-liturgical text. Most often this replacement was performed in the full copies of late Russian group.